Development of an Ethnobotanical Encyclopedia on the Antar Ajong Ceremony - Lisa Prawati; Ari Sunandar; Anandita Eka Setiadi (Jurnal Penelitian Pendidikan IPA, 2024)
The Antar Ajong ceremony is a ritual before planting rice carried out by the Sambas Malay Tribe. Plant diversity in the Antar Ajong ceremony can be developed in the form of an encyclopedia to support learning at school. This study aims to measure the validity of the media and student responses to the encyclopedia developed. The research used Research and development (R&D) with a modified 4D development model that includes the define, design, and develop stages. Data collection used interviews, observations, and questionnaires. The data was analyzed using a Likert questionnaire. The validation test obtained a value from media experts of 96.88% (very valid), material experts of 91.66% (very valid), and linguists of 88.14% (very valid). Students gave very good responses to the small-scale (99.35%) and large-scale (98.25%) trials. So it can be concluded that the ethnobotanical encyclopedia media at the Antar Ajong ceremony of the Malay Tribe of Paloh District, Sambas Regency, is feasible to apply in learning and get a positive response. This encyclopedia medium can also be used as a medium for preserving the local wisdom of the Paloh Paloh District Malay community at the Antar Anjong ceremony.